Willa and Wade. 1, Willa and Wade and the way-up-there - Henderson, Judith (Henderson, Judith. Willa and Wade, 2024)
"When Willa and Wade see a bird fly by, they feel the pull of the sky. But Willa is an ostrich and Wade is a penguin. Can they reach their lofty goal? In this first book of a new graphic novel series for early readers, two dreamers try different ways -- from pirouettes to pogo sticks -- to get off the ground."--